Boron-Doped MXenes as Electrocatalysts for Nitrogen Reduction Reaction: A Theoretical Study - Wang, Yuan; Qian, Xu; Zheng, Guokui; Tian, Ziqi; Zhang, Qiuju (Frontiers in Chemical Engineering, 2021)
Electrocatalytic nitrogen reduction reaction (NRR) is a promising and sustainable approach for ammonia production. Since boron as an active center possesses electronic structure similar to that of transition metals with d-orbitals (J. Am. Chem. Soc., 2019, 141 (7), 2884), it is supposed to be able to effectively activate the triple bond in N2. MXenes can be applied as substrates due to the large specific surface area, high conductivity and tunable surface composition. In this work, the catalytic performance of a series of MXenes supported single boron atom systems (labeled as B@MXenes) have been systematically studied by using density functional theory (DFT). B@Nb4C3O2, B@Ti4N3O2 and B@Ti3N2O2 were screened out owing to outstanding catalytic activity with limiting potentials of -0.26, -0.15, and -0.10 V, respectively. Further analysis shows that the unique property of boron that can intensely accept lone pair and back-donate the anti-bond of nitrogen contributes to the activation of inert triple bond. This work provides a new idea for the rational design of NRR catalyst and is of great significance for the future development of nitrogen reduction catalysts.